Hippuristanol - A potent steroid inhibitor of eukaryotic initiation factor 4A - Cencic, Regina (Translation (Austin), 2016)
Protein synthesis and its regulatory signaling pathways play essential roles in the initiation and maintenance of the cancer phenotype. Insight obtained over the last 3 decades on the mechanisms regulating translation in normal and transformed cells have revealed that perturbed control in cancer cells may offer an Achilles' heel for the development of novel anti-neoplastic agents. Several small molecule inhibitors have been identified and characterized that target translation initiation – more specifically, the rate-limiting step where ribosomes are recruited to mRNA templates. Among these, hippuristanol, a polyhydroxysteroid from the gorgonian Isis hippuris has been found to inhibit translation initiation by blocking the activity of eukaryotic initiation factor (eIF) 4A, an essential RNA helicase involved in this process. Herein, we highlight the biological properties of this compound, its potential development as an anti-cancer agent, and its use to validate eIF4A as an anti-neoplastic target.